Early Nephropathy Screening as a Health Seeking Behavior Among Type 2 Diabetes Mellitus Patients: A Phenomenological Study in Southwestern Uganda - Ritah Kiconco; Robert Kalyesubula; Naomi Sanyu; Bosco Bekiita Agaba; Erick Nyakundi Ondari; Deusdedit Tusubira; Gertrude N Kiwanuka (Journal of Multidisciplinary Healthcare, 2025)
Background: Nephropathy screening is vital in type 2 diabetes mellitus (T2DM) management to prevent complications, yet uptake remains low in resource-limited settings like Southwestern Uganda. This study explored the barriers and facilitators influencing screening among T2DM patients and providers at the diabetic clinic of Mbarara Regional Referral Hospital. Methods: A qualitative cross-sectional study guided by a phenomenological approach to explore lived experiences around nephro pathy screening was conducted. Fifteen adult T2DM patients in care for ≥12 months and five healthcare providers (doctors, nurses, and a laboratory technician) were purposively sampled. Semi-structured, in-depth interviews were conducted. Data were analyzed using an inductive approach. Socio-demographics; including age, sex, education, and employment were collected. All interviews were audio- recorded, transcribed verbatim, and thematically analyzed using Dedoose (version 10.0.25). Study reporting adhered to the COREQ 32-item checklist. Results: Patients described diabetes as a burdensome and life-altering condition. Key barriers to nephropathy screening included financial constraints, lack of transport, limited awareness, and dissatisfaction with care. Despite these challenges, facilitators such as proactive provider encouragement, community outreach, and availability of free testing motivated screening uptake. Providers emphasized their critical role in educating patients and detecting nephropathy but reported systemic constraints, including staff shortages, equipment failures, limited knowledge on new disease trends and screening protocols. Both groups highlighted the need for routine integration of nephropathy screening into diabetes care and greater support from the health system. Conclusion: Nephropathy screening behaviors among T2DM patients are influenced by perceived disease severity, provider communication, and systemic barriers such as cost and infrastructure. While both patients and providers recognize the value of early detection, sustained screening is hindered by resource limitations and inconsistent implementation. Strengthening institutional capacity, integrating screening into routine care, and enhancing patient-provider engagement are essential to reducing the burden of diabetic nephropathy in the study setting.
Keywords: Type 2 diabetes; Nephropathy screening; Health-seeking behavior; Barriers; Facilitators; Qualitative study; Uganda